An assessment of requirements in investments, new technologies, and infrastructures to achieve the SDGs - Walter Leal Filho and Diogo Guedes Vidal and Chen Chen and Maria Petrova and Maria Alzira Pimenta Dinis and Peter Yang and Steven Rogers and Lorena Alvarez-Castañón and Ilija Djekic and Ayyoob Sharifi and Samara Neiva (Environmental sciences Europe, 2022)
Background: The implementation of the Sustainable Development Goals (SDGs) requires much planning and the provision of resources, especially regarding the necessary investments, technologies and infrastructures needed. Yet, it is presently unclear how available these elements are, what gaps exist, what changes have taken place in terms of their availability since the adoption of the SDGs and what their requirements will be in the future. The knowledge gap has become even more concerning because of the impact of the COVID-19 pandemic. Using a bibliometric analysis, an assessment of the global progress of SDG implementation and requirements, identifying challenges through the development of a matrix, and a set of 11 case studies to triangulate the holistic analysis, an assessment of the global progress of the SDGs implementation and the impact of the COVID-19 pandemic on this process was carried out. Results: The findings suggest that the scope and width of resources limitation are currently undermining the implementation of the SDGs. Apart from the fact that the pace of progress has been insufficient, the potential of the SDGs in pursuing sustainability and improving life quality is not fully realised. This trend suggests that a substantial acceleration of the efforts is needed, especially for the five SDGs whose progress since 2015 has not been optimal, namely SDG2, SDG11, SDG13, SDG15, and SDG16, while SDG3, SDG7, SDG9, SDG14, and SDG17 show signs of progress. The case studies showed that different industries have dissimilar effects on achieving the SDGs, with the food sector correlating with 15 SDGs, as opposed to the energy sector correlating with 6 SDGs. Accordingly, the priority level assessment in terms of achieving the SDGs, points to the need to further advance the above-mentioned five SDGs, i.e., 2, 11, 13, 15 and 16. Conclusions: This study fills in a knowledge gap in respect of the current need for and availability of investments, new technologies, and infrastructures to allow countries to pursue the SDGs. It is suggested that this availability is rather limited in specific contexts. In respect of the needs to be addressed, these include resource-related constraints, limited technologies and infrastructures, affecting SDG2, SDG11, SDG13, SDG15, and SDG16, whose progress needs to be enhanced. Since the global progress in the process of implementation of the SDGs depends directly and indirectly on addressing the resource gaps, it is suggested that this topic be further investigated, so that the present imbalances in the three dimensions of sustainable development: the economic, social and environmental, be adequately addressed.
Keywords: Achievement of UN SDGs; Bibliometric analysis; Case studies; Infrastructural challenges; Investment challenges; Technological challenges